Physical activity, sedentary behaviour and cardiometabolic disease risk among adults living with obstructive sleep apnoea: Is there a case for exercise as an adjunct therapy? - Brand, Batsheva (Department of Human Biology, 2025)
Background: Sleep disorders, and resultant poor sleep quality, have emerged as being related to cardiometabolic disease (CMD) risk, including obesity, hypertension, type 2 diabetes mellitus (T2DM), and cardiovascular disease (CVD). Obstructive sleep apnoea (OSA) is the second most common sleep disorder and is characterized by multiple obstructive apnoea episodes (i.e. cessation of breathing due to complete collapse and occlusion of the upper airways), hypopnoea events (i.e. partial collapse and occlusion of the upper airways) and respiratory effort-related arousals during sleep. OSA is diagnosed using an overnight polysomnography (PSG) sleep study. The resultant Apnoea Hypopnoea Index (AHI) is used to determine the severity of OSA and reflects the number of both apnoeic or hypopnoeic events occurring per hour of sleep. Mild OSA is defined as AHI scores of 5-15, moderate OSA by scores of 15-30 and severe OSA by scores ≥30. Given the promising evidence base for the role of exercise as an adjunct therapy for OSA patients, we would ultimately like to design and implement an exercise intervention, particularly in the public healthcare setting in South Africa where access to CPAP therapy is constrained. Due to the paucity of data for patients with OSA in South Africa, we propose the current formative study to first describe OSA severity, CMD risk and habitual physical activity (PA) levels among individuals with OSA. As mentioned above, the primary treatment of OSA is positive airway pressure (PAP) therapy, with CPAP being the most common. This, together with the role of obesity in the disease, has seen the adjuncts such as exercise and dietary interventions become of even greater significance for the clinical management of these individuals living in a low income setting while seeking supportive routes. Therefore, the aim of this study is to compare PA levels, sedentary behaviour, sleep and CMD risk characteristics of adults with OSA (OSA group) to age- and gender-matched adults without OSA (CON group). This will be achieved through three objectives: 1. To systematically review the nature and efficacy of exercise interventions. 2. To characterise the CMD risk profile of both groups utilising anthropometry (BMI, waist circumference), physiological measures (resting BP and HR) and medical history (diagnosed chronic conditions and medication use). 3. To objectively measure and compare PA levels, sedentary behaviour, and habitual sleep patterns between the OSA and CON groups using wrist-worn accelerometery. 4. To explore associations between PA and CMD risk in the OSA and CON groups. Methods: A systematic review was used to assess all current studies evaluating the efficacy of an exercise program on reducing OSA severity and improving subsequent quality of life and minimising cardiometabolic risk factors in patients with OSA (e.g., improving fitness and reducing BMI and daytime sleepiness). In addition, the key components of these exercise interventions (e.g., mode of exercise, duration, frequency, intensity) were analysed on improving health outcomes in OSA patients. The main study included, thirty seven participants placed within one of two groups; the Obstructive Sleep Apnoea (OSA) group comprising of both male and female adults (n=18), previously diagnosed with moderate to severe OSA (AHI>15), and a control (CON) group comprising of both male and female adults (n=19) with no previous diagnosis of OSA nor symptoms or signs of OSA as confirmed on a validated OSA screening questionnaire (STOP-Bang, Chung, 2016), matched to the OSA group for ages (18y to 65y) and sex. Participants were excluded if they were ambulatory (i.e., makes use of any walking aid), reported any recent (2 month) change in their usual PA or sleep habits. Exclusion criteria for the CON group also included (i) a previous diagnosis of OSA (AHI ≥5), (ii) a STOP-Bang score of >4 or (iii) an affirmative answer to the STOP-Bang question. Participants for both groups were recruited from the greater Cape and Johannesburg Metropolitan areas. All participants were informed of the study purpose, risks and benefits and provided written informed consent indicating willingness to take part in the study. This study was approved by the University of Cape Town's Faculty of Health Sciences Human Research Ethics Committee (Ref: 142/2021) and was performed under strict Covid-19 regulations. In this cross-sectional observational study, all participants completed a detailed questionnaire. The investigator measured their weight, height, waist, and neck circumferences, resting BP and HR. Participants were then given a small wrist-worn accelerometer to wear for the next seven days to measure their habitual sleep, PA and sedentary habits and asked to simultaneously complete a sleep and PA diary. They returned the sleep monitor and diary on their second visit to the laboratory eight days later. Results: The present systematic review indicated that PA is an effective intervention in reducing OSA severity, improving cardio-vascular fitness, reducing important cardiometabolic risk factors and quality of life in OSA patients. The optimal combination of aerobic training and resistance exercises could also be better defined to enhance the development of exercise programs in OSA patients. The main finding of this study was that there is a similarity between the total sedentary and light activity counts and hours per day, among the OSA and CON groups, but the key differences lie in the moderate and vigorous PA settings. This suggests that the higher PA level of the CON group, implying that a lower BMI, fewer chronic conditions, and a more acceptable blood pressure reading, are significant factors contributing to their lower incidence of suffering from OSA. Conclusion: The gold standard for OSA treatment is CPAP, which reduces hypoxias. The systematic review indicated that exercise alone gives a limited benefit, (example: reducing BMI). The cardio metabolic system will benefit from effective exercise, but it will not treat OSA, rather reducing the risk of side effects of OSA. In order to optimize risk factor control and reduce long-term morbimortality, there is also a strong need for combined treatment strategies for OSA patients.